Long-tailed macaque (Macaca fascicularis) contraception methods: a systematic review - Muhammed Mikail; Tengku Azizan, Tengku Rinalfi Putra; Mohd Noor, Mohd Hezmee; Abu Hassim, Hasliza; Che’Amat, Azlan; Ab Latip, Mohd Qayyum (Multidisciplinary Digital Publishing Institute, 2023)
The contraception-based approach to wildlife management is a humane and effective alternative to population control methods. Wildlife management only has a few conventional ways to control overpopulation, such as culling, translocation, poisoning, and allowing natural death. Nevertheless, these methods usually have short-term, lethal, and unethical effects. The present systematic review aims to review the knowledge on contraception reported in long-tailed macaques as an alternative to population control. We obtained 719 records from searching CABI, PubMed, ScienceDirect, and Scopus electronic databases. After the screening and selection process, according to PRISMA guidelines, 19 articles that met the eligibility criteria were chosen. Of the 19 articles, 15 were studies on female long-tailed macaque contraception methods (six (6) hormonal and nine (9) non-hormonal). We analyzed four (4) selected articles on male Cynomolgus monkey contraception methods (two (2) hormonal and two (2) non-hormonal). One of the nine (9) articles on female long-tailed macaque contraception reports negative results. Furthermore, only two (2) studies used free-ranging long-tailed macaques as test subjects, while seventeen (17) tested on captive ones. The challenges of long-tailed macaque contraception identified in this review were the effectiveness of the contraceptive, the administration route, the economic feasibility, the distinction between captive and free-ranging Cynomolgus macaques, the choice of permanent or reversible contraception, the capability of contraceptive use for population control, and the lack of studies on the free-ranging long-tailed macaque. Notwithstanding the literature gap on long-tailed macaque contraception for population control, long-tailed macaque contraception exhibits potential as an alternative method to culling long-tailed macaque. Future research should address these obstacles to support the long-tailed macaque contraception as an alternative population control method.